Peningkatan Literasi Sastra Siswa Sekolah Dasar melalui Media Digital dan Pendekatan Kontekstual: Improving Elementary School Students' Literary Literacy through Digital Media and a Contextual Approach - Melia Mardi; Desmimi Eka Putri; Yasmanelly Yasmanelly; Ineng Naini; Gusnetti Gusnetti (ITScience (Information Technology and Science), 2025)
Elementary school students' interest in reading and appreciation of literary works remains low. Literature learning is considered abstract, boring, and unrelated to children's daily lives. However, literature plays a crucial role in shaping character, broadening linguistic horizons, and fostering empathy and creativity. As students live in a digital age, learning approaches need to be tailored to the characteristics of a generation accustomed to interactive and visual media. Therefore, learning strategies are needed that connect literary values to the real world and technology relevant to students' daily lives. This study employed a qualitative method with a descriptive approach. Data collection techniques included classroom observation, interviews, and documentation, involving elementary school teachers and students as research subjects. The focus of observations was on the literature learning process, which integrates digital media and a contextual approach. The results showed that integrating digital media and a contextual approach in literature learning increased students' interest in reading, increased their active involvement in class discussions, and increased their understanding of literary texts such as poetry, fables, and folktales. Teachers also found it helpful in delivering material because digital media can explain literary content visually and engagingly. The integration of digital media with a contextual approach has proven effective in improving elementary school students' literacy. This strategy can be used as an innovative learning alternative to build literary appreciation and character in students from an early age.